2022
DOI: 10.1002/ps.6798
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and fungicidal activity of novel N‐substituted piperazine‐containing phenylpyridines against cucumber downy mildew

Abstract: BACKGROUND Cucumber downy mildew (CDM) is a severe plant disease and affects the yield of cucumber production worldwide. As the resistance toward conventional fungicides is emerging as a ubiquitous issue, it is urgent to discover efficient fungicides with unique structures. RESULTS In this study, a series of novel phenylpyridine derivatives were designed and synthesized. Bioassays revealed that most of these compounds possessed excellent fungicidal activities against CDM. Among the phenylpyridine compounds, 2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Compound A21 , which showed the highest antifungal activity, was selected for highest occupied molecular orbtial–lowest unoccupied molecular orbital (HOMO–LUMO energy gap and molecular electrostatic potential (MEP) calculations using Gaussian 5.0.8. , The B3LYP functional and 6-31+G­(d) basis sets were adopted for all calculations. The visualization of the orbitals for compound A21 was achieved using Multiwfn and VMD software …”
Section: Methodsmentioning
confidence: 99%
“…Compound A21 , which showed the highest antifungal activity, was selected for highest occupied molecular orbtial–lowest unoccupied molecular orbital (HOMO–LUMO energy gap and molecular electrostatic potential (MEP) calculations using Gaussian 5.0.8. , The B3LYP functional and 6-31+G­(d) basis sets were adopted for all calculations. The visualization of the orbitals for compound A21 was achieved using Multiwfn and VMD software …”
Section: Methodsmentioning
confidence: 99%
“…Compound 25 had good inhibitory activity against cucumber downy mildew, with an EC 50 value of 4.40 mg/L. In addition, the nitrogen atom of the cyano group on the pyridine ring of compound 25 was in the negative electrode region, which not only easily forms hydrogen bonds, but also can electrostatically interact with potential receptors [51]. Research on molecular electrostatic potential may further guide structure optimization.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…In greenhouse experiments, these compounds were investigated for their ability to control Tetranychus cinnabarinus. Even though the bioassays demonstrated that the compounds did not exhibit acaricidal activities, most of them showed disease control activities against cucumber downy mildew, with compound 281 identified as the most potent derivative after optimization. , …”
Section: Epiloguementioning
confidence: 99%
“…Even though the bioassays demonstrated that the compounds did not exhibit acaricidal activities, most of them showed disease control activities against cucumber downy mildew, with compound 281 identified as the most potent derivative after optimization. 176,177 Thus, adopting and applying the concept of bioisosterism more overtly and broadly offers an additional avenue to the design of potentially useful agrochemicals. While piperazines are poorly represented in agrochemical design and the close homologue piperidine is exploited only sparingly, it is interesting to note that a 1,8-diazaspiro [4.5]decane moiety, a known piperazine/homopiperazine bioisostere from the medicinal chemistry literature, is embedded in insecticide and acaricide spiropidion (274).…”
Section: Epiloguementioning
confidence: 99%